Peningkatan Mutu Pembelajaran dan Prestasi Belajar Siswa Pada Bidang Studi Matematika dan Kendalanya Di Sekolah - Rina Fadliah (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2018)
The high student learning outcomes reflect the quality of the organization of learning in the school concerned. Thas way every school is required to be to improve student learning outcomes as a mirror of success in the implementation of teaching and learning process so far. In this case school need to make varios preparations and improvement in order create an effective learning situation and easily accepted by student so that in the end  can provide the desired results. In reality in class not necessarily many who understand and understand about the subject matter of mathematics provided by the teacher, if there is even limited to a few people not the whole class that undersand. This is obstacle in the learning Mathimatics, student get saturated faster so that thier concentration is split, because a calculation is more difficult to memorize than sentence paragraph.